Integrating bioactivity and molecular simulations to explore the pharmacological landscape of Lagerstroemia speciosa leaf extract - Md Shajedul Haque; Rubel Ahmad; Bidhan Chandra Sarkar; Manoshi Sana; Hasi Rani Saha; Niranjan Kumar Sana (PLoS ONE, 2025)
Natural resources are vital for identifying novel treatments for noncommunicable diseases and multidrug-resistant pathogens. Lagerstroemia speciosa (L. speciosa) Linn. is traditionally used to manage conditions like diabetes, cancer, and oxidative stress-related diseases. Current studies frequently lack comprehensive bioactivity assessments coupled with molecular simulation analyses of L. speciosa leaf extracts. We aimed to assess the phytochemical profiling, bioactivity, in silico pharmacological properties, and molecular interactions of L. speciosa leaf extracts prepared using organic solvents. Methanol (5.1) and ethanol (4.3) extracts yielded the highest concentrations of total phenolics, flavonoids, and proanthocyanidins due to their high polarity indices. Antioxidant activities were robustly evaluated using DPPH, ABTS, superoxide, and nitric oxide assays, with the ethanol extract demonstrating significant free radical scavenging (IC 50 = 75.53 µg/mL for DPPH). The methanol extract exhibited broad-spectrum antibacterial activity against multidrug-resistant strains, including Escherichia coli and Staphylococcus aureus , alongside moderate antifungal activity against Candida albicans and Saccharomyces cerevisiae . The brine shrimp lethality assay revealed moderate cytotoxicity (LC 50 = 601.8 µg/mL), suggesting potential anticancer properties likely mediated by bioactive compounds such as ellagic acid and gallic acid. Methanol and ethanol extracts of L. speciosa significantly inhibited α-amylase and α-glucosidase compared to standard acarbose, indicating substantial antidiabetic potential by delaying carbohydrate digestion and reducing postprandial glucose levels. Complementary molecular docking and ADME pharmacokinetic studies provided in silico support for the observed antioxidant, antimicrobial, antidiabetic, and chemopreventive activities. The compelling evidence collectively suggests that L. speciosa extracts are a promising source of bioactive compounds.